Designing optimal set of experiments by using bayesian method in methyl iodide adsorption - Zainuddin, Zaitul Marlizawati (Mathematics Department, UTM, 1999)
This paper deals with the design and analysis of the best sets of experiments by using Bayesian Method in the presence of prior knowledge. However, the model presented is not completely general since it is restricted to solve this particular problem, that is to find the best conditions to adsorp Methyl Iodide released after a nuclear reaction.